(Ba, Sr)LaZnTaO6:Mn4+ far red emitting phosphors for plant growth LEDs: structure and photoluminescence properties. (3rd April 2020) - Huang, Dayu; Dang, Peipei; Xiao, Xiao; Bai, Biao; Lian, Hongzhou; Zeng, Qingguang; Lin, Jun
Abstract : Application of (Ba, Sr)LaZnTaO6 :Mn 4+ far red light emitting LEDs in plant lighting Abstract : It is necessary to develop novel high-efficiency red or far-red-emitting LEDs in order to facilitate the phosphor-converted light-emitting diodes (pc-LEDs) for plant growth. This work reports a series of novel far-red emitting (Ba, Sr)LaZnTaO6 : x Mn 4+ phosphors with double perovskite structure synthesized by the traditional high-temperature solid-state reaction (SSR). The crystal structure and morphology of (Ba, Sr)LaZnTaO6 were investigated by high-resolution TEM, SEM, and XRD Rietveld refinement. The photoluminescence properties were systematically explored and analyzed by diffuse reflectance (DR) spectra, photoluminescence emission (PL) and excitation (PLE) spectra, decay curves, and temperature-dependent spectra. Mn 4+ ions occupy Ta 5+ sites located at the [TaO6 ] octahedral emitting red light with the peak at 698 nm in BaLaZnTaO6 :Mn 4+ and 695 nm in SrLaZnTaO6 :Mn 4+ under n-UV and blue light excitation. The critical quenching concentration of Mn 4+ was determined to be 0.008. The concentration quenching mechanism could be a dipole–dipole interaction between the Mn 4+ ions. In addition, the PL intensity of (Ba, Sr)LaZnTaO6 : x Mn 4+ phosphors decreases with increasing temperature. The SrLaZnTaO6 : x Mn 4+ sample has better thermal stability than BaLaZnTaO6 : x Mn 4+ . Interestingly, (Ba, Sr)LaZnTaO6 :0.008Mn 4+ exhibits outstanding internal quantum efficiency (IQE ≥ 80%). Finally, the fabricated LEDs were combined with SrLaZnTaO6 :0.008Mn 4+ phosphors combined with 460 nm InGaN chips, which emit blue and red light. Based on the above properties, the rare-earth-free (Ba, Sr)LaZnTaO6 : x Mn 4+ phosphors have great potential in being applied as far-red emitting phosphors in high-power plant growth LEDS.